IBM INTRODUKSI SISTEM PENGOLAHAN SAMPAH MODEL JEPANG DALAM RANGKA MENDUKUNG GREEN CAMPUS DI LPPM - Adhitya Pitara Sanjaya; Bara Yudhistira; Sulistyo Saputro (Jurnal Kewirausahaan dan Bisnis, 2017)
Institute for Research and Community Service (LPPM) is one ofimplementing element of Sebelas Maret University which has the task ofcoordinating, monitoring, and assessing the implementation of researchactivities and community service organized by the Centers in Institute forResearch and Community Service. One of the missions of LPPM UNS is toimprove the ability and the role of lecturers and students in research andempowerment of the community. One of the problems, can not be handled inthe community is waste problem. Currently, public awareness to do wastesegregation has not been done maximally, so it needs to do stimulus to raisethe awareness. The results of the survey have been done in LPPM and Facultyof Agriculture UNS. The phenomenon of waste disposal is found to be lazy todispose of garbage (35%), unavailable garbage (41%), waste bins (15%) anduninspiring waste (9% ). Further activities are training to students to designthe trash in accordance with the Japanese model that is by making trashesbased on the type of paper waste, plastic waste, garbage cans and wetgarbage.